Penurunan Aktivitas Proliferasi Sel Adenokarsinoma Mamma Mencit C3H akibat Pemberian Ekstrak Etanol Lengkuas (Alpinia galanga) - Susanto Winarko; Yanwirasti .; Aswiyanti Asri; Salmiah Agus (Perhimpunan Dokter Spesialis Patologi Indonesia (IAPI), 2016)
Background WHO data in 2011 showed that deaths from breast cancer in Indonesia reached 20,052 peoples of all deaths. This is partly due to the high cost of treatment, so that many people are turning to alternative therapies such as traditional plants. Lengkuas (Alpinia galanga (L) Wild is the traditional material that is cheap and easily available in Indonesia. Lengkuas-containing active substances I-acetoxychavicol acetate (ACA), and according to past research has anti-cancer properties by inhibiting the activity through the inhibition of cell proliferation pathways nuclear factor kappa B (NFÆ™B). To investigate the effect of ethanol extract of lengkuas against mammary adenocarcinoma cell prolifferation activities in C3H mice with various dose levels. Methods This study was an experimental study using C3H mice with post-test only research design controlled group design. Experimental animals consisted of 32 C3H mice were inoculated with tumor cells and then divided into 4 groups: control group (K) and three treatment groups (P1, P2 and P3) were given graded doses of ethanol extract of lengkuas 225 mg/kgBW/day, 450 mg/kgBW/day and 675 mg/kgBW/ day for 2 weeks. After all mice were terminated, examined the proliferative activity of tumor cells with Ki-67 antibody. Differences in proliferative activity between the groups were tested using one-way anova followed by post hoc Bonferroni test. Results There were significant differences in proliferative activities (p=0.000) among the four groups. By the post hoc Bonferroni analysis was found the significant differences in proliferative activities between the control group P1, with P2 controls, P3 control group, between P1 with P3 group, P2 with P3 group (p=